1982
DOI: 10.1029/ja087ia11p09171
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial plasma bubbles: Vertically elongated wedges from the bottomside F layer

Abstract: We address the question regarding the two‐dimensional shape of equatorial plasma bubbles in the plane transverse to the geomagnetic field. By comparing the east‐west spatial relationship of ion‐density depletions measured in‐situ by the Atmospheric Explorer E (AE‐E) satellite to backscatter plumes measured by the ALTAIR radar, we show that plasma bubbles are vertically elongated depletions that extend upward from the bottom side of the F layer, in the form of tilted wedges, rather than more isotropically shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
167
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(189 citation statements)
references
References 32 publications
(72 reference statements)
22
167
0
Order By: Relevance
“…The characteristics and morphology of these depletions, that has been obtained mainly with the Jicamarca radar (e.g. Woodman and La Hoz, 1976), and substantiated by the satellite-based instruments and Altair radar observations (McClure et al, 1977;Dyson and Benson, 1978;Muldrew, 1980;Tsunoda, 1980;Tsunoda et al, 1982;Kil and Heelis, 1998;Yeh et al, 2001), are very well documented. Theoretical and observational investigations indiCorrespondence to: R. Pandey (pandey r@yahoo.com) cate that these depletions are generated on the bottomside of the nighttime equatorial F region and rise to higher altitudes due to the non-linear evolution of the generalized RayleighTaylor and E×B plasma instabilities (Kelley, 1989;Fejer et al, 1999).…”
Section: Introductionmentioning
confidence: 92%
“…The characteristics and morphology of these depletions, that has been obtained mainly with the Jicamarca radar (e.g. Woodman and La Hoz, 1976), and substantiated by the satellite-based instruments and Altair radar observations (McClure et al, 1977;Dyson and Benson, 1978;Muldrew, 1980;Tsunoda, 1980;Tsunoda et al, 1982;Kil and Heelis, 1998;Yeh et al, 2001), are very well documented. Theoretical and observational investigations indiCorrespondence to: R. Pandey (pandey r@yahoo.com) cate that these depletions are generated on the bottomside of the nighttime equatorial F region and rise to higher altitudes due to the non-linear evolution of the generalized RayleighTaylor and E×B plasma instabilities (Kelley, 1989;Fejer et al, 1999).…”
Section: Introductionmentioning
confidence: 92%
“…As pointed out by Tsunoda et al (1982), a unique feature found to play a major role in the equatorial spread-F phenomena is the plasma "bubble", a localized depletion in F-region electron density. Plasma bubbles are aligned magnetic flux tubes and cover north-south distances across the magnetic equator of several thousand kilometers, with east-west dimensions of up to a few hundred kilometers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the nonlinear evolution, these instabilities would fully develop into vertically elongated wedges of plasma depletion from bottomside to topside of the F-layer (e.g. Tsunoda et al, 1982;Zalesack et al, 1982;Sultan, 1996).…”
Section: Introductionmentioning
confidence: 99%